Waste PET-MOF-Cleanwater Waste PET-Derived Metal-Organic Framework (MOFs) as Cost-Effective Adsorbents for Removal of Hazardous Elements from Polluted Water - Ren, Jianwei; Nomngongo, Philiswa Nosizo; Jen, Tien-Chien (UJ Press, 2022)
In counties like South Africa, firstly, the waste PET stream has posed a serious problem to the environment, and the current recycling of waste PET remains as low as 30%. The waste PET recycling industries such as PETCO & Extrupet (South Africa) are struggling to implement innovative processes to make cooperate more profitable. Secondly, metal-organic frameworks (MOFs) as a new class of porous materials, the MOFs-based water treatment holds the promises to provide cost-effective solutions dealing with the polluted water. However, the high costs of MOFs production have raised a challenge for its effective implementations. Given that, cross-cutting advances in materials and engineering will help to solve those societal challenges. To maintain the world-class research and development associated with human capacity in South Africa, this multidisciplinary and transdisciplinary work has been strengthened along with the basic-applied research continuum under the frame of South Africa (NRF)/Poland (NCBR) Joint Science and Technology Research Collaboration.